Perancangan Kursi Puzzle untuk Anak-Anak dengan Sistem Knockdown - Evelyn Nadia Setyawan (Intra, 2017)
In general, children spending their times with plays and trying new things. In this periods child should doing many things so they can grow optimally. However, gadgets make them don't do what they actually need to do for their physical development, they rely on their little 10 fingers and parents miss the chance to look at their child physical development. Based on the problems that had been described, we realized that we need a cooperation between parents and their children, we need something that attracts children to think and move. Through this knockdown system puzzle chair design, we can use it to improve the cooperation between parents and their children, improving their(child) creativity, and stimulates their(child) motoric, Because this chair is designed not only used as usual chair but also used as children toys.